High-Stability Foam of Silica Nanofluid to Overcome Liquid Loading in Enhancing Natural Gas Production - Ajiz, Hendrix Abdul; Mawarani, Lizda Johar; Widiyastuti, Widiyastuti; Setyawan, Heru (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2021)
One of the promising solutions to overcome the liquid loading problem in natural gas production is using a foaming agent. The extreme condition in the gas well causes the foam used tends to break up. Therefore, it is required to enhance the foam stability by adding a stabilizer agent. This research aims to investigate the effect of silica nanoparticles as a surfactant stabilizer to obtain a high-stability foam using silica nanofluid. Silica nanofluid was synthesized from sodium silicate solution by the solgel method. Then, the colloidal silica was added to the surfactant solution without a coupling agent. The effects of aging time and silica concentration were investigated. The results show that the surface tension tends to increase with the increase of aging time and silica concentration but decrease in foam stability which is indicated by a decrease in the foam half-life time. The best foam stability is obtained in silica nanofluids with an aging time of 6 hours and a silica concentration of 30 ppm, which shows a foam half-life of 42 hours and can improve foam stability with several parameters representing the conditions of the gas well